Biochemical study of diseases related to blood disorders (Eurasian Journal of Research, Development and Innovation, 2024)
There is no cure for hemophilia yet, but by giving the treatment mentioned above, people with hemophilia can live a normal life. Without treatment, it will be difficult for people with severe hemophilia to go to school or work regularly. These people can become disabled, have problems walking or doing simple activities, or even die prematurely